National electrical code 1996 (NFPA (Series), 1995)
Revised every three years, the National Electrical Code (NEC) is the most widely used and accepted criteria for all electrical installations. The book contains the up-to-the-minute facts and safety guidelines which students and electricians need to avoid costly errors and get installations and inspections right the first time.